Motivasi Dan Pemberdayaan Masyarakat Dalam Pengembangan Usaha Aren Di Desa Rumah Sumbul, Kecamatan Sibolangit, Kabupaten Deli Serdang - Batubara, Ridwanti; Affandi, Oding; Ismayadi, Ismayadi; Purba, Ridhoi Meilona; Syahputra, Orang Kaya Hasnanda; Suryati, Irsa’; Irmawati, Irmawati; Utami, Rahmi; Sari, Yasmine Anggia; Warjio, Warjio; Anggraini, Novita (PPPM POLTESA, 2024)
Community empowerment is very important in developing businesses to increase their income. In empowering the community, it needs to be motivated by conducting motivational training. The purpose of the Community Service activities carried out is to motivate the community, especially in increasing palm sap water processing business activities and increasing knowledge and business skills independently by utilizing natural resources in the village. The method of this activity is education and motivation in the form of material delivery and training in assisting the community to develop business. The results of the activity based on questionnaires, the participants were motivated and would participate in the development of the palm business according to their capacity, especially in processing palm sugar sap water into palm sugar processing business. It is expected that the implementation of this activity can improve the creative economy of the community.